Broadband emission phosphor Sr3Al2O5Cl2:Bi3+: Luminescence modulation and application for a white-light-emitting diode. Issue 22 (15th November 2022) - Ma, Haotian; Guan, Li; Yin, Tao; Wu, Yue; Liu, Zhenyang; Wang, Dawei; Wang, Fenghe; Fu, Nian; Li, Xu
Abstract: Bi 3+ ions can regulate and control the fluorescence of a phosphor by transferring energy to the activating agent or occupying different luminescent centers, which is important for modifying phosphors and revealing fluorescence mechanisms. As a base material, Sr3 Al2 O5 Cl2 has three types of Sr sites (Sr 1, Sr 2, and Sr 3) that may be occupied by Bi 3+ ions (Sr 2+ has a similar radius to Bi 3+ ). Herein, we successfully synthesized a series of Sr3 Al2 O5 Cl2 :x%Bi 3+ phosphors using the high-temperature solid-state method and determined a two-site-occupying emission mechanism. X-ray diffraction patterns indicated that the samples were synthesized well, and Rietveld refinement results provided their structural information. Photoluminescence spectra showed 490 nm (λex  = 345 nm) and 556 nm (λex  = 376 nm) emission peaks, which might arise from different luminescent centers. The concentration quenching study, peak separation analysis, fluorescence lifetime spectra, and diffuse reflection spectra indicated that the Bi 3+ ions occupied two of the three Sr sites. Calculations of relative system energies and distortion index proved that the occupation only occurred in the Sr 1 and Sr 3 sites, and crystal splitting analysis determined that Sr 1 site generated 490 nm emission light and Sr 3 site generated 556 nm emission light. The charge compensator and flux were added to enhance the fluorescence intensity of the phosphor, and 5% K + along with 1% BaF2 is the optimal dosage. Finally, the SrAlSiN3 :Eu 2+, BaMgAl10 O17 :Eu 2+, and optimized Sr3 Al2 O5 Cl2 :5%Bi 3+ phosphors were combined as a luminous layer and a warm-white light-emitting diode was realized; the color rendering indices were 84.3, 85.8, 86.4, and 86.2 under working currents of 20, 30, 40, and 50 mA, respectively. Graphical abstract: Image 1